A New, Simple, One-Pot Route for the Synthesis of Triazepin-8-one Derivatives - Zeng, Hui; Zhang, Xiao; Deng, Yayun; Chang, Yaning; Shao, Xusheng; Xu, Xiaoyong; Li, Zhong (Synlett, 2016)
A novel procedure for constructing triazepin-8-one skeletons under mild conditions in one pot was developed. The access to triazepin-8-ones was achieved via direct amination of imidazol-6-ones with aqueous ammonia and cyclization with formaldehyde. The experimental simplicity and moderate to good yields are the main features of this method.
Keywords: imidazol-6-ones; one-pot; triazepin-8-one; ring-opening; cyclization